Four phylogenetic species of ergot from Canada and their characteristics in morphology, alkaloid production, and pathogenicity. (2nd September 2020) - Liu, Miao; Overy, David P.; Cayouette, Jacques; Shoukouhi, Parivash; Hicks, Carmen; Bisson, Kassandra; Sproule, Amanda; Wyka, Stephen A.; Broders, Kirk; Popovic, Zlatko; Menzies, Jim G.
ABSTRACT: Four ergot species ( Claviceps ripicola, C. quebecensis, C. perihumidiphila, and C. occidentalis ) were recognized based on analyses of DNA sequences from multiple loci, including two housekeeping genes, RNA polymerase II second largest subunit ( RPB2 ), and translation elongation factor 1-α ( TEF1-α ), and a single-copy ergot alkaloid synthesis gene ( easE ) encoding chanoclavine I synthase oxidoreductase. Morphological features, ergot alkaloid production, and pathogenicity on five common cereal crops of each species were evaluated and presented in taxonomic descriptions. A synoptic key was also provided for identification.